Control of prosthetic hands : challenges and emerging avenues - Nazarpour, Kianoush (Healthcare technologies series, 2020)
This edited book brings together research from laboratories across the world, offering a global perspective on advances in prosthetic hand control. State-of-the-art control of prosthetics in laboratories and clinical spaces are presented and challenges discussed, and effects of user training on control of prosthetics are also highlighted.